Sponsorship of oncology clinical trials in the United States according to age of eligibility - Dylan V. Neel; David S. Shulman; Clement Ma; Florence Bourgeois; Steven G. DuBois (Cancer Medicine)
Abstract Background The sponsorship mix of trials relevant to young people with cancer has not been reported. Understanding this sponsorship mix may have implications for policies and regulations related to pediatric cancer drug development. Methods We analyzed sponsorship of interventional trials first opened in the United States from 2007 to 2018 using the ClinicalTrials.gov registry. A total of 51 781 trials across non‐oncology disciplines and 18 431 oncology trials were classified according to lower age of eligibility (≥18 years vs < 18 years). Studies were stratified according to sponsorship (industry vs non‐industry). Trial characteristics were compared by sponsorship category. Trends in sponsorship were tracked over time. Results Within oncology trials for patients ≥ 18 years, sponsorship was 33% industry and 67% non‐industry. Among oncology trials that included patients < 18 years, sponsorship was 16.6% industry and 83.4% non‐industry (P < .001). 15.5% of industry‐sponsored trials in non‐oncology disciplines included patients < 18 years, whereas only 5.2% of industry‐sponsored oncology trials were open to patients < 18 years (P < .001). Relative to trials with non‐industry sponsors, there was a statistically significant increase in industry sponsorship of oncology trials that included patients < 18 years over time (P < .001). Trial characteristics differed significantly according to sponsor type regardless of age of eligibility. Conclusions Interventional oncology trials that include patients < 18 years are less likely to be industry‐sponsored compared to oncology trials exclusively in patients ≥ 18 years. Compared to other medical disciplines, a smaller proportion of industry‐sponsored oncology trials included patients < 18 years. Trial sponsorship is associated with differential trial characteristics, such as trial duration and number of patients enrolled, regardless of age.